Cold Exposure Induces Proliferation of Mature Brown Adipocyte in a ß3-Adrenergic Receptor-Mediated Pathway. - Keigo Fukano; Yuko Okamatsu-Ogura; Ayumi Tsubota; Junko Nio-Kobayashi; Kazuhiro Kimura (PLoS ONE, 2016)
Hyperplasia of brown adipose tissue (BAT) is a fundamental mechanism for adaptation to survive in the cold environment in rodents. To determine which cell types comprising BAT contribute to tissue hyperplasia, immunohistochemical analysis using a proliferative marker Ki67 was performed on the BAT from 6-week-old C57BL/6J mice housed at 23°C (control) or 10°C (cold) for 5 days. Interestingly, in the control group, the cell proliferative marker Ki67 was detected in the nuclei of uncoupling protein 1-positive mature brown adipocytes (7.2% ± 0.4% of brown adipocyte), as well as in the non-adipocyte stromal-vascular (SV) cells (19.6% ± 2.3% of SV cells), which include preadiopocytes. The percentage of Ki67-positive brown adipocytes increased to 25.6% ± 1.8% at Day 1 after cold exposure and was significantly higher than the non-cold acclimated control until Day 5 (21.8% ± 1.7%). On the other hand, the percentage of Ki67-positive SV cells gradually increased by a cold exposure and peaked to 42.1% ± 8.3% at Day 5. Injection of a ß3-adrenergic receptor (ß3-AR) agonist for continuous 5 days increased the number of Ki67-positive brown adipocytes even at Day 1 but not that of SV cells. In addition, the ß3-AR antagonist, but not ß1-AR antagonist, attenuated the cold exposure-induced increase in the number of Ki67-positive brown adipocytes. These results suggest that mature brown adipocytes proliferate immediately after cold exposure in a ß3-AR-mediated pathway. Thus, proliferation of mature brown adipocytes as well as preadipocytes in SV cells may contribute to cold exposure-induced BAT hyperplasia.